Size structure, reproductive condition, length-weight relationship and biomass of Cryphiops caementarius (Decapoda: Palaemonidae) in Peruvian coastal rivers - Flores-Gómez, Stive (2021)
The aim of this study was to determine the population structure, sex ratio, reproductive condition, population index and biomass of Cryphiops caementarius in the Cañete (Lima), Tambo, Ocoña and Majes (Arequipa) rivers, Peru. The research was carried out based on information obtained by the Instituto del Mar del Perú. The biologicalpopulation analysis was carried out from prawn samples obtained by systematic captures in different altitude strata. The water quality parameters presented values that were within the acceptable ranges for the normal development of the resource. The modal sizes of the resource were less than 70 mm (minimum catch size) in the Cañete, Tambo and Majes rivers. A higher proportion of males was determined in the Cañete, Tambo and Ocoña rivers, and a lower proportion in the Majes river. The proportion of spawning females was less than 10% in the evaluated months (July-December 2019). The relative growth coefficient of prawns was higher in males than in females in the Tambo, Ocoña and Majes rivers, and similar in males and females in the Cañete river. The Majes was the river with the highest biomass in relation to the other rivers and, therefore, the most productive. The high biomass in the different altitudinal strata of the rivers was associated with high concentrations of oxygen and total hardness of the water. The information from this research is of value in guiding sustainable fisheries management strategies.